Capacity, Vulnerability, and Informed Consent for Research. Issue 1 (March 2018) - Biros, Michelle
This article presents an overview for clinician investigators on the concepts of decision-making capacity and vulnerability as related to human subjects research. Tools for capacity assessment and unacknowledged sources of vulnerability are discussed, and the practical gaps in current informed consent requirements related to impaired capacity and potential vulnerability are described. Options are suggested for research discussions when full regulatory consent is not possible and an exception from informed consent does not apply.